2021
DOI: 10.21791/ijems.2021.2.7.
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandémia hatása a munkavállalók fizikai aktivitására

Abstract: A globalizáció, az elmúlt évek robbanásszerű technológia fejlődése jelentősen átalakította az emberek életvitelét, melynek következtében az ülő életmódot folytató emberek száma megemelkedett. A koronavírus világjárvány tovább tetézte a helyzetet és példa nélküli állapotot eredményezett a világban. A járvány kitörésével az otthoni munkavégzés jelensége egyre inkább elterjedt a világban, ami negatív hatással lehet a munkavállalók életmódjára, mely az üléssel töltött idő növekedéséhez és a fizikai aktivitás csökk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
(11 reference statements)
1
1
0
5
Order By: Relevance
“…Analyzing the results of our study sample, it is clear that even the sporting habits of elite athletes, recreational athletes and professionals with multiple roles were negatively affected by COVID-19, as the weekly sporting frequency and physical activity levels of participants decreased during the period of curfew, compared to the period before curfew. The results of an online cross-sectional study by Ráthonyi and colleagues, similar to our study, demonstrated a decrease in physical activity and an increase in sedentary time during the pandemic [12].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Analyzing the results of our study sample, it is clear that even the sporting habits of elite athletes, recreational athletes and professionals with multiple roles were negatively affected by COVID-19, as the weekly sporting frequency and physical activity levels of participants decreased during the period of curfew, compared to the period before curfew. The results of an online cross-sectional study by Ráthonyi and colleagues, similar to our study, demonstrated a decrease in physical activity and an increase in sedentary time during the pandemic [12].…”
Section: Discussionsupporting
confidence: 90%
“…We wondered whether the sports community could maintain this level of pre-quarantine exercise habits with alternative solutions in this unusual situation, as some authors have found associations between physical activity decline, curfew restriction and the lockdown period [9][10][11]. Ráthonyi's study found that adult workers had decreased physical activity levels and increased sedentary time during lockdowns [12]. Szabó and colleagues also came to a similar conclusion for sportspeople [9].…”
Section: Introductionmentioning
confidence: 95%
“…A globalizáció, az elmúlt évek robbanásszerű technológiafejlődése jelentősen átalakította az emberek életvitelét, melynek következtében az ülő életmódot folytató emberek száma megemelkedett (Ráthonyi et al 2021). A Coronavírus világjárvány kitörésével az otthoni munkavégzés jelensége egyre inkább elterjedt a világban, mely az üléssel töltött idő növekedéséhez és a fizikai aktivitás csökkenéséhez vezethet.…”
Section: Irodalmi Feldolgozásunclassified
“…Az e-sportolók versenyzés, edzés vagy mérkőzések elemzése közben is ülő tevékenységet végeznek a számítógép előtt, így az egészségüket meghatározza, hogy mellette mennyi fizikai aktivitást végeznek. Az elmúlt években az emberek életvitele is ebbe az irányba változott, elsősorban a fejlett országokban megemelkedett az ülő életmódot folytató emberek száma [12], [21]. Ülő tevékenységnek elsősorban az ülő, hátradőlt vagy fekvő testhelyzetű cselekvést tekintjük, melyek energiaigénye nem haladja meg az 1,5 MET (metabolikus ekvivalens) értéket [13].…”
Section: Video Game Skills Physical Activity and Other Health-related...unclassified